2022
DOI: 10.1021/acs.chemmater.2c00722
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Electrolyte Interphase of Molecular Crowding Electrolytes

Abstract: Molecular crowding electrolytes extend the stability window of aqueous batteries with water-miscible/soluble polymers at a low concentration of lithium salts [2 m lithium bis­(trifluoromethane sulfonyl)­imide (LiTFSI)]. Water decomposition [especially hydrogen evolution reaction (HER)] is effectively suppressed, enabling the use of numerous negative electrodes which cannot work in traditional aqueous electrolytes. However, the mechanism underlying the cathodic stability of molecular crowding electrolytes is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…40 They further demonstrated that in this LiTSI-based molecular crowding electrolyte, an insoluble LiF-rich SEI was successfully constructed, which was crucial in suppressing the HER in ALIBs. 388 Polyacrylamide (PAM) was introduced into a highly concentrated electrolyte (21 M LiTFSI in water) by Li et al to boost the electrochemical performance of ALIBs. The appearance of PAM in the primary solvation sheath of Li + not only reduced free water near the interface, but also promoted the formation of the anion-derived SEI, significantly boosting the cycling stability of LTO/LMO full cells with 86% retention after 100 cycles.…”
Section: Moderate Solvating Electrolytes Alibsmentioning
confidence: 99%
“…40 They further demonstrated that in this LiTSI-based molecular crowding electrolyte, an insoluble LiF-rich SEI was successfully constructed, which was crucial in suppressing the HER in ALIBs. 388 Polyacrylamide (PAM) was introduced into a highly concentrated electrolyte (21 M LiTFSI in water) by Li et al to boost the electrochemical performance of ALIBs. The appearance of PAM in the primary solvation sheath of Li + not only reduced free water near the interface, but also promoted the formation of the anion-derived SEI, significantly boosting the cycling stability of LTO/LMO full cells with 86% retention after 100 cycles.…”
Section: Moderate Solvating Electrolytes Alibsmentioning
confidence: 99%
“…However, the redox potential of the Mo 6 S 8 anode was still lower than the HER onset potential of the LHCE, which would trigger H 2 O decomposition during the battery cycling and thus reduce the battery reversibility. This may be attributed to the absence of highly electronically insulating LiF derived from LiTFSI in the SEI layer, which has been widely evidenced in ALIBs [7a,e,38] . Ren et al.…”
Section: Hybrid Aqueous/non‐aqueous Electrolytesmentioning
confidence: 96%
“…in Materials Science & Engineering from National Tsing Hua University and a Ph.D. also in Materials Science & Engineering from the Massachusetts Institute of Technology. She is a member of Chemistry of Materials ’ Editorial Advisory Board, and her work appears regularly in the journal, with a recent example comparing the suppression of the hydrogen evolution reaction with molecular crowding electrolytes to traditional electrolytes …”
Section: Yi-chun Lumentioning
confidence: 99%